2020
DOI: 10.1136/gpsych-2019-100159
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional and herbal supplements in the treatment of obsessive compulsive disorder

Abstract: Obsessive-compulsive disorder (OCD) is a neuropsychiatric disorder that is characterised by obsessions and compulsions. The recommended treatments for OCD are cognitive– behavioural therapy using exposure and response prevention and/or pharmacotherapy. On the other hand, some nutritional and herbal supplements may be effective in the treatment of OCD. Nutritional and herbal supplements in OCD treatment will be reviewed in this paper. PubMed (Medline), Cochrane Library and Google Scholar databases were reviewed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 73 publications
(71 reference statements)
1
10
0
Order By: Relevance
“…Multiple hypotheses regarding possible pathophysiological mechanisms of these mood disorders included altered neurotransmission, chemical imbalance in the brain, inflammation, reduced neuroplasticity, chronic stress, and nutrient deficiency (Berridge, 2017; Maletic et al., 2007; Pertile, Cui, Hammond, & Eyles, 2018). Extensive research over the past decades has shown a critical role of malnutrition in depression and anxiety disorder (Kuygun Karci & Gul Celik, 2020; Milaneschi et al, 2019; Sanchez‐Villegas et al., 2009). Moreover, this body of research has supported a complex involvement of vitamin D (VD) deficiency in mood disorders (Ju, Lee, & Jeong, 2013); however, the relationship between the two was not fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple hypotheses regarding possible pathophysiological mechanisms of these mood disorders included altered neurotransmission, chemical imbalance in the brain, inflammation, reduced neuroplasticity, chronic stress, and nutrient deficiency (Berridge, 2017; Maletic et al., 2007; Pertile, Cui, Hammond, & Eyles, 2018). Extensive research over the past decades has shown a critical role of malnutrition in depression and anxiety disorder (Kuygun Karci & Gul Celik, 2020; Milaneschi et al, 2019; Sanchez‐Villegas et al., 2009). Moreover, this body of research has supported a complex involvement of vitamin D (VD) deficiency in mood disorders (Ju, Lee, & Jeong, 2013); however, the relationship between the two was not fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have corroborated the fact that deficiency of some vitamins and other essential nutrients lead to cognitive impairments ( 126 , 127 ). Vitamin D plays an important role in immunity modulation, inflammatory response, and antioxidant processes, as well as in normal brain development and functioning, neurotransmission, neuroprotection, proliferation, and differentiation ( 80 , 128 , 129 ). Vitamin D deficiency can be associated with numerous neuropsychiatric diseases, including autism, major depressive disorder, schizophrenia, and Obsessive-Compulsive Disorder (OCD) ( 130 , 131 ).…”
Section: Foods and Food Compounds That Affect Psychiatric Biomarkersmentioning
confidence: 99%
“…Although some studies found no evidence for the efficacy of myoinositol in OCD treatment, others have reported the effectiveness of myoinositol supplementation in the treatment of OCD ( 78 , 138 ). Available clinical evidence suggests that MI may potentially be effective as monotherapy in OCD ( 80 ). The suggested mechanisms of action involve modulation of the reuptake of serotonin and an increase in 5-HT2 receptor density ( 79 ).…”
Section: Foods and Food Compounds That Affect Psychiatric Biomarkersmentioning
confidence: 99%
See 2 more Smart Citations